2020
DOI: 10.1080/1744666x.2020.1732820
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and epigenetic regulation of natural resistance to HIV-1 infection: new approaches to unveil the HESN secret

Abstract: Since the identification of HIV, several studies reported the unusual case of small groups of subjects showing natural resistance to HIV-infection. These subjects are referred to as HIV-1-exposed seronegative (HESN) individuals and include people located in different regions of the world, with diverse ethnic backgrounds and routes of exposure. The mechanism/s responsible for protection from infection in HESN individuals are basically indefinite and most likely are multifactorial. Areas coveredHost factors, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 176 publications
(195 reference statements)
0
8
0
Order By: Relevance
“…It is also important to underline that following long-term antiretroviral therapy HIV-patients display an altered lipid profile which can result in dyslipidemia [44], and that disease progression was shown to be delayed in HIV-infected patients showing increased cholesterol metabolism and reduced cholesterol synthesis [45][46][47]. being mediated by the upregulation of several ISGs [3,4,21] among which, CH25H is suggested to play a pivotal role. The expression of this enzyme, which catalyzes the formation of 25HC from cholesterol [48] was, indeed, significantly augmented in both uninfected and in vitro HIV-1-infected PBMCs and MDMs from HESN and is likely to be at least in part responsible for the 25HC-dependent upregulation of LXR and downregulation of SREBP1 [21,35], as we observed in our experimental setting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also important to underline that following long-term antiretroviral therapy HIV-patients display an altered lipid profile which can result in dyslipidemia [44], and that disease progression was shown to be delayed in HIV-infected patients showing increased cholesterol metabolism and reduced cholesterol synthesis [45][46][47]. being mediated by the upregulation of several ISGs [3,4,21] among which, CH25H is suggested to play a pivotal role. The expression of this enzyme, which catalyzes the formation of 25HC from cholesterol [48] was, indeed, significantly augmented in both uninfected and in vitro HIV-1-infected PBMCs and MDMs from HESN and is likely to be at least in part responsible for the 25HC-dependent upregulation of LXR and downregulation of SREBP1 [21,35], as we observed in our experimental setting.…”
Section: Discussionmentioning
confidence: 99%
“…These individuals, referred to as HIV-1-exposed seronegative (HESN) have the extraordinary capacity to remain HIV-1 uninfected despite frequent risk behaviors, including injection drug use with needle sharing or sexual intercourse with infected partners [1,2]. Natural protection to HIV-1 infection has been associated with a wide range of genetic and immunological factors [3][4][5]. In particular, several publications reported a strong correlation between HIV-1 infection, resistance and the presence of an immune activation status [4,6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such high-risk subjects are referred to as HIV-exposed seronegative (HESN) individuals and include sex workers, HIV-status discordant couples, intravenous drug users, and children born to untreated HIV-infected mothers. Relative resistance to HIV infection is likely multi-factorial and several studies have identified innate immune and anti-inflammatory factors, HIV-specific T-and B-cell responses, increased regulatory T-and B-cell activity as well as genetic and epigenetic correlates to this phenotype [2][3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Whether these reflect an unknown resistance to infection in selected population subsets is currently unknown. Recruited caregivers may have personal factors that do not allow SARS-CoV-2 infection as demonstrated in HIV infection where genetic and epigenetic factors are involved in natural resistance to infection ( 14 ). Further investigations are needed to evaluate these factors.…”
Section: Discussionmentioning
confidence: 99%